1984
DOI: 10.1083/jcb.98.5.1878
|View full text |Cite
|
Sign up to set email alerts
|

A new method of preparing embeddment-free sections for transmission electron microscopy: applications to the cytoskeletal framework and other three-dimensional networks.

Abstract: Diethylene glycol distearate is used as a removable embedding medium to produce embeddment-free sections for transmission electron microscopy. The easily cut sections of this material float and form ribbons in a water-filled knife trough and exhibit interference colors that aid in the selection of sections of equal thickness . The images obtained with embeddment-free sections are compared with those from the more conventional epoxyembedded sections, and illustrate that embedding medium can obscure important bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 19 publications
(17 reference statements)
1
89
1
Order By: Relevance
“…This is the preparation used for examining mitotic cells. Further extraction with a mixture ofTween 40 Mitotic cells were extracted only with Triton X-100 in CSK buffer, since the compaction of chromatin into chromosomes obviates the need for DNA extraction. To preserve the spindle microtubules, taxol was added to the mitotic cell culture medium 5 min before extraction.…”
Section: Methodsmentioning
confidence: 99%
“…This is the preparation used for examining mitotic cells. Further extraction with a mixture ofTween 40 Mitotic cells were extracted only with Triton X-100 in CSK buffer, since the compaction of chromatin into chromosomes obviates the need for DNA extraction. To preserve the spindle microtubules, taxol was added to the mitotic cell culture medium 5 min before extraction.…”
Section: Methodsmentioning
confidence: 99%
“…It subsequently was dehydrated, embedded in modified diethylene glycol distearate (supplied by the EMCorp under the name ''Antibed;'' the company no longer exists, and an alternative supplier is being sought) and sectioned to a thickness of 90 nm. The sections were placed on Formvar-covered, carbon-coated copper grids, and the embedding material then removed (9). A JEOL 1200 EXII microscope operated at 80 kV was used to view the resinless sections.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the resinless section can image the entire sample in three dimensions and does not require heavy-metal stains. Also, the support of the sample by the embedding medium has proven unnecessary; once chemically fixed, cell structures are strong and possessed of considerable dimensional stability (8,9).…”
mentioning
confidence: 99%
“…Electron microscopy has long been applied to plant cell research, but why such intercellular connection has not been definitely observed up to now? According to Penman and his colleagues [4], this ignorance may be due to the obscurity caused by embedding medium to biological structures. The definite chemical characteristics of these intercellular cytoskeletons, the way they pass through cell wall, the role they play in plant tissue and the possibility of their developmental change etc, all need further investigation.…”
Section: Fmentioning
confidence: 99%
“…Since then, cytoskeleton became one of the front fields in cell research, and many important findings have been obtained, contributing a great deal to the development of cell biology [3]. However, some important biological structures, especially protein filaments, may be obscured by using the conventional epoxy-embedding medium [4,5]. Furthermore, ultrathin section technique can reveal only 2-dimensional views, so it is difficult to explore the exact organization of whole cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%